Advanced robotics and additive manufacturing of composites: towards a new era in Industry 4.0. Issue 5 (4th April 2022) - Parmar, Hetal; Khan, Tayyab; Tucci, Fausto; Umer, Rehan; Carlone, Pierpaolo
ABSTRACT: In recent years, new revolutionary paradigms generally indicated using the term Industry 4.0, have been conceived and are progressively applied in several manufacturing systems to achieve a smarter, more effective, and sustainable production. This article aims to depict the present and future scenarios related to the application of Industry 4.0 concepts to polymer composites manufacturing. To provide a view on future potential, and open new research frontiers, the article attempts to address through elaborate discussions two major questions: What is the future of fiber-reinforced polymer composites manufacturing in the Industry 4.0 context? What are the recent and potential developments in robotic and additive manufacturing of advanced fiber-reinforced composites? The article, in addition, connects new avenues in additive manufacturing, for instance, incorporating topology optimization, design opportunities, recent industrial developments in machines and patent disclosures, and defect detection/mitigation during manufacture. Similarly, recent developments concerning robotic Automated Fiber/Tape Placement have been provided, discussing state-of-the-art research trends and future opportunities.